(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was conducted to know the effect of parity, stage of lactation and udder morphology on milk yield and milk constituents in Jaffarabadi buffaloes. A total of 150 buffaloes selected from private dairy farms located in and around Hyderabadwere utilized. The average daily milk yield (ADMY) recorded in buffaloes with different parities were 7.06 ± 0.16, 8.11 ± 0.11, 8.86 ± 0.12and 8.23 ± 0.08 Kg in first, second, third and fourth parity, respectively showing the third parity animals yielded higher ADMY compared to other parities. The ADMY in different lactation stages recorded were 8.55 ± 0.14, 8.23 ± 0.12 and 8.08 ± 0.13 Kg in early, mid and late stage of lactation, respectively showing there was a decrease in ADMY from early to late stage of lactation. There was a positive and highly significant (P<0.01) correlation between the udder morphology and ADMY. The average milk fat, solids non fat (SNF) and total solids (TS) of different parities ranged from 7.41 ± 0.12 to 8.05 ± 0.09%, 9.67 ± 0.09 to 10.03 ± 0.12% and 17.44 ± 0.22 to 17.72 ± 0.15%, respectively. The overall average milk fat, SNF and TS were found to be 7.81 ± 0.05, 9.77 ± 0.05 and 17.58 ± 0.08 %, respectively showing there was an increase in milk fat and TS from first parity to fourth parity. The average milk fat, SNF and TS in different stages of lactation ranged from 7.24 ± 0.08 to 8.35 ± 0.08, 9.67 ± 0.07 to 9.85 ± 0.10 and 16.91 ± 0.12 to 18.20 ± 0.12 %, respectively and a significant (P<0.05) increase in milk fat and TS from early to late lactation stage was observed. Similarly, SNF also increased from early to late stage of lactation but was insignificant. It was also observed that there was no significant effect of udder and teat shapes on milk constituents. There was a negative correlation of ADMY with milk fat, SNF and TS and correlation were highly significant (P<0.01) in case of ADMY with fat and TS. The milk fat was positively correlated with SNF and TS but the correlation was significant only with TS. The study concludes that, parity and stage of lactation affect ADMY and milk constituents, while the positive correlation among milk constituents indicating that selection for one trait will also improve other traits in Jaffarabadi buffaloe